Newborn with spontaneous rupture of an infected cephalohematorma - Shorofsky, Michael J.; Bhatia, Darshita (International Journal of Contemporary Pediatrics, 2018)
Cephalohematomas present in approximately 2% of newborns and rarely become infected. In this case we present a newborn who presented with spontaneous rupture of an infected cephalohematoma with E. Coli. The patient subsequently developed scalp osteomyelitis secondary to the infected cephalohematom. In this case report we will go over the presentation and the mamangement of the case.